Anti-biofilm activity of the tick-derived antimicrobial peptide Os(11-22)NH2 against candida albicans ATCC 90028 - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2019.